Online social networks human cognitive constraints in Facebook and Twitter personal graphs - Arnaboldi, Valerio; Passarella, Andrea; Conti, Marco; Dunbar, Robin I.M (Computer science reviews and trends, 2015)
Online Social Networks: Human Cognitive Constraints in Facebook and Twitter provides new insights into the structural properties of personal online social networks and the mechanisms underpinning human online social behavior. As the availability of digital communication data generated by social media is revolutionizing the field of social networks analysis, the text discusses the use of large- scale datasets to study the structural properties of online ego networks, to compare them with the properties of general human social networks, and to highlight additional properties